2018
DOI: 10.1016/j.jcma.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Contributing factors to mortality rates of pulmonary tuberculosis in intensive care units

Abstract: The mortality of TB patients who needed ICU support remains high. This higher mortality rate seems related to multi-organ failure, requiring invasive mechanical ventilation and high APACHE II scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…In a recent study done on TB patients requiring ICU admission, mortality was 72.5% (Tatar et al 2018).…”
Section: Critical Care Of Patients With Tbmentioning
confidence: 98%
“…In a recent study done on TB patients requiring ICU admission, mortality was 72.5% (Tatar et al 2018).…”
Section: Critical Care Of Patients With Tbmentioning
confidence: 98%
“…[12] Factors significantly associated with mortality in the present study included a higher APACHE II score, hypolbuminaemia and thrombocytopenia, concurring with previous studies. [2,10,11,13] Moreover, Tatar et al [11] and Ryu et al [14] identified an APACHE II score of >18 and >20, respectively, as being predictive of death. The mean APACHE II score of 23.8 (21.2% for survivors v. 26.3% for non-survivors) in our study highlights the high disease acuity in our cohort, a finding consistent with other studies with predominantly mechanically ventilated patients.…”
Section: Researchmentioning
confidence: 99%
“…The need for mechanical ventilation in critically ill patients with TB is associated with increased mortality and prolonged ICU and hospital stays. [10] Tatar et al [11] reported a mortal ity rate of 80.5% in 36 of 40 patients requiring mechanical ventilation in an ICU in Turkey, while in India, an ICU mortality rate of 44% was observed in 57 mechanically ventilated patients. [10] We previously reported ICU mortality and hospital mortality of 44% and 59%, respectively.…”
Section: Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Delays in diagnosis and treatment of pulmonary TB are principal causes of death, especially in patients with acute respiratory failure. 11 , 19 , 20 Early diagnosis and start of effective treatment is needed to prevent ICU admission and complications. 9 It is imperative that the absorption of anti-TB treatment is maximised; a challenge in the critically ill individual.…”
Section: Introductionmentioning
confidence: 99%